On the Articulation of Witchcraft and Modes of Production among the Nupe, Northern Nigeria - Dirk Kohnert (Witchcraft in Modern Africa: Witches, Witch-Hunts and Magical Imaginaries, 2007)
The political economy of occult belief in Africa can highlight hidden social and political conflict in times of transition which remain otherwise undetected. This has been demonstrated in taking the development of witchcraft accusations over time as indicator, and the Nupe of Northern Nigeria as an example. A tentative long-term study on the growth of the Nupe state since pre-colonial times points towards a close relationship between the content and form of witchcraft accusations and the mode of production under which the stakeholders used to life and work. Over time, witchcraft accusations among the Nupe apparently served different, even antagonistic ends, depending on the mode of production in which they were embedded. Much confusion in literature on the apparent contradiction between `emancipating' and `oppressive' functions of witchcraft beliefs could be avoided by considering this articulation between modes of production, witchcraft accusations, and the underlying vested interests of the ruling powers. – – RÉSUMÉ "Sur l'articulation de la sorcellerie et de modes de production parmi les Nupe, dans le nord du Nigéria": L'économie politique de la croyance occulte en Afrique peut mettre en évidence des conflits sociales et politiques cachés en période de transition qui restent autrement inaperçus. Cela a été démontré à prendre le développement des accusations de sorcellerie au fil du temps comme indicateur, et les Nupe du Nigeria du Nord comme un exemple. Une étude préliminaire à long terme sur la croissance de l'État Nupe depuis l'époque précoloniale pointe vers une relation étroite entre le contenu et la forme des accusations de sorcellerie et le mode de production en vertu de laquelle les parties prenantes ont travaillés. Au fil du temps, les accusations de sorcellerie parmi les Nupe ont apparemment servis différents, voire antagonistes objectives, selon le mode de production dans lequel ils ont été intégrés. Beaucoup de confusion dans la littérature sur la contradiction apparente entre des croyances de sorcellerie « émancipateur » et des fonctions plutôt « oppressives » pourrait être évité en prenant en compte cette articulation entre les modes de production, les accusations de sorcellerie, et les intérêts sous-jacents des puissances dominantes.
Keywords: Z1; Z12; Z13; O55; 330; occult belief systems; Africa; Nigeria; Nupeland; modes of production; witchcraft